Electronic properties of α-graphyne nanotubes. (April 2015) - Kang, Baotao; Lee, Jin Yong
Abstract: We constructed α-graphyne nanotubes (αGyNTs) and performed density functional theory calculations to investigate the electronic properties of zigzag and armchair αGyNTs. We found that all zigzag graphyne nanotubes (Z-αGyNTs) were semiconductors. In particular, the band gap of Z-αGyNTs showed an oscillatory dependence on tube size which could be further classified into three families with Nz  = 3 m − 1, 3 m and 3 m + 1 where m is a positive integer. This resulted in band gap magnitudes in the following rank order: 3 m − 1 > 3 m + 1 > 3 m. Armchair αGyNTs were also calculated to be semiconductor with very small band gaps when tube size is small, though they become metallic as the tube size increases.